2017
DOI: 10.1016/j.bpj.2017.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of an Inside-Out Folding Intermediate of T4 Phage Sliding Clamp

Abstract: Protein folding process involves formation of transiently occurring intermediates that are difficult to isolate and characterize. It is both necessary and interesting to characterize the structural conformations adopted by these intermediates, also called molten globules (MG), to understand protein folding. Here, we investigated the equilibrium (un)folding intermediate state of T4 phage gene product 45 (gp45, also known as DNA polymerase processivity factor or sliding clamp) obtained during chemical denaturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…SDM was carried out to generate all the mutants using transfer-PCR (polymerase chain reaction) ( 48 , 55 ). PCR was carried out using mutagenic primers and plasmids harboring respective WT genes as templates.…”
Section: Methodsmentioning
confidence: 99%
“…SDM was carried out to generate all the mutants using transfer-PCR (polymerase chain reaction) ( 48 , 55 ). PCR was carried out using mutagenic primers and plasmids harboring respective WT genes as templates.…”
Section: Methodsmentioning
confidence: 99%
“…Although NMR can provide structural information at amino acid resolution, limited insights have been obtained about transient nonnative states using NMR because of the longer time associated with NMR measurements. Nevertheless, a few studies have reported the 2D NMR characterization of the DMG state because it populates under equilibrium under high pressure (31,58,59). The CcdB_4 and high-pressure ubiquitin state are compact as judged by the dispersion of crosspeaks.…”
Section: Ccdb_4 Is Well Folded and Native-likementioning
confidence: 99%